2020
DOI: 10.20883/jofa.34
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between BMI and the severity of facial wrinkles — preliminary study

Abstract: Introduction. The severity of facial wrinkles is related to many factors, such as: endogenic skin aging (innate mechanisms), the influence of external factors (photoaging) and lifestyle factors such as smoking or body weight.Aim. The aim of the study is to determine the relationship between BMI and the occurrence of various types of facial wrinkles.Material and Methods. 50 people participated in the study, including 9 men and 41 women. The criteria for participation in the study were: age over 18, no visible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A study carried out across Europe also showed that lower body mass index was significantly associated with wrinkling. This is possibly because those with facial fat are those with higher BMI as fat has a filler effect [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out across Europe also showed that lower body mass index was significantly associated with wrinkling. This is possibly because those with facial fat are those with higher BMI as fat has a filler effect [18,19].…”
Section: Discussionmentioning
confidence: 99%